The Burger International - Featherstone, Liza (Labour / Le Travail, 1999)
Discusses efforts to unionize fast-food workers, in particular the drive at the McDonald's in Squamish, BC. [Note: The workers voted to decertify less than a year later, before a collective agreement was signed.]